Kajian Partisipasi Anggota pada Kegiatan Kelompok Tani Hutan di Desa Kedung Poh Kecamatan Nglipar Kabupaten Gunung Kidul - Saputro, Setiaji Heri; Budiharjo, Kadarwati (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2024)
Most of the people who own community forests in Gunung Kidul, in their management, have formed Forest Farmers Groups (KTH), which aim to improve living standards and the economy through businesses in the forestry sector. Member participation in activities carried out by KTH is one of the approaches for KTH in generating ideas/ideas/programs in the context of solving problems for its members, increasing social awareness, improving human resources, and regeneration. This research aims to determine the extent of participation of KTH members in Kedungpoh village, Nglipar Gunung Kidul District in their activities and determine the correlation with their sociodemographic conditions. The method used in this research is a survey method which is analyzed using correlation analysis and crosstab. This research shows that the level of participation of members of the Forest Farmers Group in their activities in planning is 78.30%, implementation is 89.88% and evaluation is 66.39%, while the socio-demographic condition of the members of the Farmers group which has a correlation in participation in activities organized by the Forest Farmers Group is age. and years of farming, which is closely related to members' motivation in participating in activities, namely to increase knowledge, receive agricultural assistance, gain experience, develop personal potential, increase enthusiasm and obtain agricultural training. This research also shows that there is a relationship/correlation between activity stages, namely between the stages of activity planning, activity implementation and activity evaluation.